Anthraquinone Derivative Reduces Tau Oligomer Progression by Inhibiting Cysteine‐Cysteine Interaction. Issue 5 (8th February 2019) - Areche, Carlos; Zapata, Francisca; González, Mathias; Díaz, Esteban; Montecinos, Rubén; Hernández, Marcos; Melo, Francisco; Cornejo, Alberto
Abstract: Tau protein is a natively unfolded protein whose primary role is to participate in axonal transport closely associated with microtubules. Neurodegenerative disorders including Alzheimer's disease and Tauopathies involved tau protein that is found hyperphosphorylated in vivo ; then, tau is detached from microtubules to form toxic aggregates or oligomers, which have a deleterious effect on membranes, triggering an inflammatory response. Considering finding tau inhibitors, we isolated two compounds in the ethyl acetate extract from Xanthoria ectaneoides (Nyl.) Zahlbr; ergosterol peroxide (1 ) and a new anthraquinone (2 ). We established the structure through spectroscopic data and biogenic considerations, and we named it "2‐hydroxy‐3‐((8‐hydroxy‐3‐methoxy‐6‐methylanthraquinonyl)oxy)propanoic acid". This new anthraquinone was evaluated as a tau inhibitor by ThT fluorescence, dot blot assays and total internal reflection fluorescence microscopy. Our results strongly suggest that this anthraquinone remodels soluble oligomers and diminishes β‐sheet content. Moreover, through the fluorescence labeling of cysteine inside of the microtubule‐binding domain (4R), we showed that this anthraquinone could reduce the oligomers progression by inhibiting cysteine interactions. Abstract : Break the habit : Tau protein is an unfolded protein linked to microtubules. However, once it detaches from microtubules, tau can interact with other tau monomers to form toxic aggregates. Since there is no cure for Alzheimer's disease nor for tauopathies, it is essential to find new tau inhibitors to serve as scaffold for drug discovery.